Progenitor/Stem Cell Fate Determination: Interactive Dynamics of Cell Cycle and Microvesicles - Aliotta, Jason M. (Mary Ann Liebert, Inc., 2012)
We have shown that hematopoietic stem/progenitor cell phenotype and differentiative potential change throughout cell cycle. Lung-derived microvesicles (LDMVs) also change marrow cell phenotype by inducing them to express pulmonary epithelial cell-specific mRNA and protein. These changes are accentuated when microvesicles isolated from injured lung. We wish to determine if microvesicle-treated stem/progenitor cell phenotype is linked to cell cycle and to the injury status of the lung providing microvesicles. Lineage depleted, Sca-1+ (Lin-/Sca-1+) marrow isolated from mice were cultured with interleukin 3 (IL-3), IL-6, IL-11, and stem cell factor (cytokine-cultured cells), removed at hours zero (cell cycle phase G0/G1), 24 (late G1/early S), and 48 (late S/early G2/M), and cocultured with lung tissue, lung conditioned media (LCM), or LDMV from irradiated or nonirradiated mice. Alternatively, Lin-/Sca-1+ cells not exposed to exogenous cytokines were separated into G0/G1 and S/G2/M cell cycle phase populations by fluorescence-activated cell sorting (FACS) and used in coculture. Separately, LDMV from irradiated and nonirradiated mice were analyzed for the presence of adhesion proteins. Peak pulmonary epithelial cell-specific mRNA expression was seen in G0/G1 cytokine-cultured cells cocultured with irradiated lung and in late G1/early S cells cocultured with nonirradiated lung. The same pattern was seen in cytokine-cultured Lin-/Sca-1 cells cocultured with LCM and LDMV and when FACS-separated Lin-/Sca-1 cells unexposed to exogenous cytokines were used in coculture. Cells and LDMV expressed adhesion proteins whose levels differed based on cycle status (cells) or radiation injury (LDMV), suggesting a mechanism for microvesicle entry. These data demonstrate that microvesicle modification of progenitor/stem cells is influenced by cell cycle and the treatment of the originator lung tissue.